Chemiresistor Sensors Based on Gold Nanoparticle Composites. (2015) - Daskal, Y.; Dittrich, R.; Walter, J.; Joseph, Y.
Abstract: On a silicon wafer equipped with interdigital electrodes, gold nanoparticles with an average size of 5 nm are assembled in a thin film using different organic linkers, either manually by layer-by-layer spin coating or automatically by layer-by-layer self-assembly in a microfluidic cell. The composition of the films is analyzed by X-ray photoelectron spectroscopy (XPS). The electrical and chemiresistive sorption properties of toluene, 1-propanol, 4-methyl-2-pentanone and water in the organic/nanoparticles composites are investigated.